2020
DOI: 10.3390/antiox9060511
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cashew (Anacardium occidentale L.) Nuts on an Experimental Model of Painful Degenerative Joint Disease

Abstract: Osteoarthritis is a progressive joint disease characterized by the activation of different molecular mediators, including proinflammatory cytokines, reactive oxygen species, metalloproteinases and nociceptive mediators. Anacardium occidentale L. is a medicinal plant with anti-oxidative and anti-inflammatory properties. In this study we evaluate the effects of cashew nuts (from Anacardium occidentale L.) oral administration on an experimental model of painful degenerative joint disease. Monosodium iodoacetate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 48 publications
0
64
1
Order By: Relevance
“…In agreement with the chemical composition of West Africa cashew [ 15 ], cashews contain a high proportion of lipid (44.19%), followed by carbohydrate (35.43%) expressed as sum of soluble sugars and fiber and protein (22.46%). The total phenolic content, expressed as mg/100 g of sample, was higher (80.01) compared to what was reported in our previous work for West Africa cashews (69.64) [ 22 ].…”
Section: Resultscontrasting
confidence: 64%
See 3 more Smart Citations
“…In agreement with the chemical composition of West Africa cashew [ 15 ], cashews contain a high proportion of lipid (44.19%), followed by carbohydrate (35.43%) expressed as sum of soluble sugars and fiber and protein (22.46%). The total phenolic content, expressed as mg/100 g of sample, was higher (80.01) compared to what was reported in our previous work for West Africa cashews (69.64) [ 22 ].…”
Section: Resultscontrasting
confidence: 64%
“…Well-known antioxidants such as quercetin, curcumin, and vitamin C protect against I/R injury [ 30 , 31 ], proposing that natural sources of antioxidants may be useful to treat this issue. Previous studies from our laboratory showed the antioxidant properties of cashew nuts in experimental model of colitis and osteoarthritis [ 15 , 22 ]. In particular, these studies showed cashew nuts’ ability to alleviate the clinical signs, pain perception, histological damage, and molecular mediators involved in these diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All sections were washed with PBS and then treated as previously reported [ 50 ]. Stained sections from each mouse were scored in a blinded fashion and observed using a Leica DM6 microscope (Leica Microsystems SpA) following a typical procedure [ 51 ]. The histogram profile is related to the positive pixel intensity value obtained [ 52 ].…”
Section: Methodsmentioning
confidence: 99%